2023
DOI: 10.36366/frontiers.v35i1.789
|View full text |Cite
|
Sign up to set email alerts
|

Online + International: Utilizing Theory to Maximize Intercultural Learning in Virtual Exchange Courses

Abstract: Virtual exchanges (VEs) are course-based experiences designed to promote global learning, often by integrating cross-cultural interactions and collaborations with people from other areas of the world into coursework in a virtual format. Due to the widespread disruption of the COVID-19 pandemic, VEs have seen an increase in popularity. However, research findings on the effectiveness of VEs are mixed, and limited guidance is available to VE instructors on how to structure and facilitate these programs. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Various article types were considered in this review, as shown in Table 2. Five of the twenty-one were theoretical or conceptual articles [8][9][10][11][12]. The majority of the articles, 13, were peer-reviewed research studies [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Article Typesmentioning
confidence: 99%
See 4 more Smart Citations
“…Various article types were considered in this review, as shown in Table 2. Five of the twenty-one were theoretical or conceptual articles [8][9][10][11][12]. The majority of the articles, 13, were peer-reviewed research studies [13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Article Typesmentioning
confidence: 99%
“…Thirteen articles were published in 2022 [8][9][10]14,15,17,18,20,[22][23][24][25]28]. Two articles reviewed were published in 2023 [12,13].…”
Section: Publications By Yearmentioning
confidence: 99%
See 3 more Smart Citations